The accounting methods of the "Opera del Duomo" of Orvieto, from its origins to the 16th century statute reform: single or double-entry bookkeeping? - Mari, Libero Mario; Picciaia, Francesca (De Computis, Revista Española de Historia de la Contabilidad., 2014)
The “Opera del Duomo” is the institution, still in existence, which was responsible for the construction of the cathedral in Orvieto. Over the centuries there have been many changes to its structure, in part due to continual conflict between the public administration and religious organizations. In accordance with the interpretation of the development of accounting as a result of its historical context, and, in particular, its organizational structure, this paper aims, through an analysis of the accounting registers and books of the Opera, to investigate “if” and “when” it is possible to observe the introduction of the double-entry bookkeeping method, and its role and function in the Opera’s structure.